Crime, Violence, and Development : Trends, Costs, and Policy Options in the Caribbean - World Bank; United Nations Office on Drugs and Crime (Washington, DC, 2012)
The report on Crime, violence, and development: trends, costs, and policy options in the Caribbean, is organized as follows. It begins with an overview of crime in the region, separately considering conventional and organized crime. Two subsequent chapters examine risk factors and the costs of crime for the region as a whole. Next, a series of chapters presents case studies designed to highlight particular issues in specific countries. These case studies were chosen in order to provide a detailed analysis of the most pressing issues that are amenable to policy making at the regional and national levels. The specific issues were chosen in consultation with stakeholders in the region to ensure that the report was responding to their demands and needs. The report ends with a chapter on public policy responses to crime in the region. The report states that through multiple channels, crime and violence threaten the welfare of Caribbean citizens. Beyond the direct effect on victims, crime and violence inflict widespread costs, generating a climate of fear for all citizens and diminishing economic growth. Crime and violence present one of the paramount challenges to development in the Caribbean. Moreover, the study believes that several factors which cut across the diverse countries of the region heighten their vulnerability to crime and violence. Primary among these is the region's vulnerability to drug trafficking. Wedged between the world's source of cocaine to the south and its primary consumer markets to the north, the Caribbean is the transit point for a torrent of narcotics, with a street value that exceeds the value of the entire legal economy. Compounding their difficulties, Caribbean countries have large coastlines and territorial waters and many have weak criminal justice systems that are easily overwhelmed. The study stress that the Governments of the Caribbean countries recognize the seriousness of the problem and are exploring innovative policy responses at both the national and regional levels. Civil society organizations are doing their part as well by designing and implementing violence prevention programs targeting youth violence, violence against women, and other important forms of violence. The report concludes that much, however, remains to be done.